Water management in rural South India and Sri Lanka Emerging themes and critical issues - Cohen, Patrice; Janakarajan, S. (Collection Sciences Sociales, 2003)
Water resources and their uses and management are - worldwide and on the regional scale of South Asia - one of the main concerns of the environmental and social equilibrium of the new century. These proceedings therefore contribute to the efforts of Indo-French and Sri Lankan-French cooperation to develop scientific collaboration on water management. The contributions by Indian, Sri Lankan and French specialists in the social sciences - historians, economists, sociologists, anthropologists, geographers - as well as specialists in agronomy, soil sciences or forestry, offer critical approaches and data from various disciplines regarding the understanding of water availability and water uses and management in South India and Sri Lanka, along with themes that emerge from these considerations.